The polonium-210 poisoning of Mr Alexander Litvinenko. (28th February 2017) - Harrison, John; Fell, Tim; Leggett, Rich; Lloyd, David; Puncher, Matthew; Youngman, Mike
Abstract: Mr Litvinenko died on 23 November 2006 after having been poisoned with polonium-210 on 1 November. Measurements of the polonium-210 content of post-mortem tissue samples and samples of urine and blood showed the presence of large amounts of 210 Po. Autoradiography of hair samples showed two regions of 210 Po activity, providing evidence of an earlier poisoning attempt during October 2006, resulting in absorption to blood of about one-hundredth of that estimated for 1 November. Intake by ingestion on 1 November was estimated to be around 4 GBq, assuming 10% absorption to blood, and the resulting organ doses reached estimated values that were generally in a range from about 20 Gy to over 100 Gy. Comparison with estimates of protracted alpha particle doses required to cause irreversible organ damage supported the conclusion that death was the inevitable consequence of multiple organ failure, with destruction of the haemopoietic bone marrow, as well as damage to kidneys and liver, being important contributors. If the earlier poisoning during October 2006 had not been followed by a second major intake on 1 November, it is possible that the earlier intake of around 40 MBq, with absorption of 4 MBq to blood, might have caused irreversible kidney damage over a prolonged period of months or years, with doses of approaching 3 Gy.